Low vision aids and age are associated with Müller-Lyer illusion in congenital visually impaired children - Lin, Na; Chen, Bichi; Yang, Maoyuan; Lu, Fan; Deng, Ruzhi (Frontiers in Psychology, 2023)
Background The correlation between visual impairment and Müller-Lyer illusion is not yet elucidated. This study aimed to explore the connection between visual status, age, and the intensity of Müller-Lyer illusion in congenitally visually impaired and visually healthy children aged 4–17 years. Additionally, the developmental trends were compared. Methods This cross-sectional study included 125 visually impaired children (age: 10.59 ± 4.05 years), among them, 53 had utilized low vision aids (LVAs) and 133 healthy controls (age: 11.33 ± 3.39 years). The participants were presented with Müller-Lyer illusion stimuli via binocular and engaged in a two-alternative forced choice task to quantify the illusion intensity. Pertinent factors including age, gender, residence, binocular distant best-corrected visual acuity and LVAs usage history, were assessed. Results The visually impaired group exhibited significantly elevated illusion intensity compared to the healthy group (9.74 ± 2.89% vs. 5.42 ± 3.81%, P < 0.001), and visually impaired participants who had used LVAs exhibited significantly lower intensity compared to those had not (9.13 ± 3.00% vs. 10.19± 2.74%, P = 0.043). Multivariate generalized estimation equations revealed that visual impairment [odds ratio (OR) = 2.75, P < 0.001] and age (OR = 0.60, P < 0.001) were associated with illusion intensity in all participants, while history of LVAs usage (OR = 0.49, P = 0.045) and age (OR = 0.61, P < 0.001) were negatively correlated in visually impaired group. A significantly negative correlation was found between illusion intensity and age 4–17 years in the subgroups of visually impaired who had used LVAs (Y = −0.54X+15.06, R² = 0.56), who had not used (Y = −0.49X+15.24, R² = 0.51), and healthy controls (Y = −0.50X+11.18, R² = 0.21); all P-values were < 0.001. Conclusion Children aged 4–17 years afflicted with congenital visual impairment exhibited a heightened intensity of Müller-Lyer illusion compared to visually normal counterparts, LVAs usage experience could reduce this higher intensity. The developmental trajectory of illusion intensity declined consistently with age across all three groups. The abnormal visual experiences during early-life may adversely affect integration in congenitally visually impaired children, and LVAs could facilitate this functional development.